2021
DOI: 10.1007/s10461-021-03537-w
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal HIV Stigma Among South Indian Mothers Living with HIV and the CD4 Count of Children Living with HIV

Abstract: HIV stigma takes a multidimensional toll on a mother’s ability to care for herself and subsequently may impact her ability to care for her child, particularly when mother and child are seroconcordant. A cross-sectional analysis was conducted to examine the association between maternal HIV stigma and child CD4 count in rural India. We assessed 108 mother–child dyads and found that a one-unit increase in community stigma fear decreased child CD4 count by 352 cells (95% CI = − 603, − 102), highlighting the need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…The prevalence of perceived HIV stigma was high, with over two-thirds (68.6%) of participants reporting experiencing stigma. This aligns with previous studies that have demonstrated the pervasive nature of HIV stigma and its detrimental effects on the well-being and health of PWH [7][8][9][10][11][12][13][14][15][16][17]. On the other hand, the prevalence of enacted stigma was relatively low (6.7%) in this setting, which contrasts with findings from previous studies in sub-Saharan Africa, which found high levels of enacted stigma towards PWH [28][29][30].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The prevalence of perceived HIV stigma was high, with over two-thirds (68.6%) of participants reporting experiencing stigma. This aligns with previous studies that have demonstrated the pervasive nature of HIV stigma and its detrimental effects on the well-being and health of PWH [7][8][9][10][11][12][13][14][15][16][17]. On the other hand, the prevalence of enacted stigma was relatively low (6.7%) in this setting, which contrasts with findings from previous studies in sub-Saharan Africa, which found high levels of enacted stigma towards PWH [28][29][30].…”
Section: Discussionsupporting
confidence: 82%
“…Enacted stigma, on the other hand, encompasses the actual experiences of discrimination, mistreatment, and marginalization faced by PWH due to their real or perceived serostatus [6]. HIV stigma can have profound impacts on the psychosocial well-being, mental health, quality of life, and clinical outcomes of PWH [7][8][9][10][11][12][13][14][15][16][17]. Studies have shown that HIV stigma leads to increased levels of depression and anxiety [7], unwillingness to test for HIV [8,9], fear of status disclosure [10,11], and poor treatment adherence [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of AIDS was not seen in the natural host species, such as the African Green Monkey. On the other hand, pathogenic species, such as the Rhesus macaque, exhibited high immune activation [35].…”
Section: Introductionmentioning
confidence: 99%